Electrochemically Engineered Mesoporous Sn-Oxide Rods for Anode Materials in Lithium-Ion Batteries - Woo-Jin Lee; Yu-Jeong Min; Heon-Cheol Shin (Applied Sciences)
Sn-based anodes for lithium-ion batteries (LIBs) offer high capacity and low cost; however, significant volume changes during lithiation/delithiation cause mechanical degradation, limiting their practical applications. Microstructural control is a key approach to mitigating these volume changes. This study reports the fabrication of core (Sn rod)-shell (mesoporous Sn-oxide layer) structures through electrodeposition followed by anodization, and their applications to anode active materials for LIBs. First, micro-Sn rods with controlled lengths and diameters were fabricated under various electrodeposition conditions. The electrodeposited Sn exhibited a dendritic structure with short secondary rods branching from a long primary rod. While the primary Sn rod diameters remained constant, the secondary rod diameters varied depending on electrodeposition parameters. Notably, rod coarsening due to secondary rod agglomeration occurred at higher currents and longer deposition durations during galvanostatic electrodeposition. In contrast, potentiostatic electrodeposition prevented agglomeration and increased the quantity of Sn rods with voltage. Subsequently, the core-shell structures were fabricated by anodizing Sn rods, forming mesoporous Sn-oxide layers with different pore sizes and pore wall thicknesses. Electrochemical characterization revealed that the core-shell anode performance for LIBs varied with the Sn-oxide shell’s microstructure. These findings provide insights into optimal core-shell structures to improve anode performance for LIBs.